Double-skinned forward osmosis membranes based on layer-by-layer assembly—FO performance and fouling behavior - Zhao, Yang (2013)
Novel crosslinked layer-by-layer (xLbL) forward osmosis (FO) membranes with a double-skinned design have been synthesized and characterized in the present work. Cross flow reverse osmosis test results showed that the membrane top skin generally had higher hydraulic resistance and better solute rejection compared to the bottom skin even when the same number of polyelectrolyte layers were deposited. The overall water permeability of the double-skinned FO membrane can be estimated from the respective values of the top and bottom skins using a resistance-in-series model. For FO tests performed at high feed solution (FS) concentration (0.5 M MgCl2), the water flux was not affected by the membrane separation properties nor its orientation. However, much higher FO water flux was obtained in the top-skin-facing-the-draw-solution (Top-DS) orientation compared to the alternative Top-FS orientation when the FS concentration was low. Using DI water as FS and 0.5 M MgCl2 as DS, FO water fluxes ranged from 40 to 80 L/m2 h in Top-DS and ∼30 L/m2 h in Top-FS. Higher DS concentrations resulted in greater FO water fluxes (e.g., 50–110 L/m2 h at 2 M MgCl2 DS). Fouling tests demonstrated that the double-skinned membrane had much better resistance against FO fouling in the Top-DS orientation. To the best knowledge of the authors, this is the first systematic study on the synthesis and characterization of double-skinned xLbL membranes. In addition, their superior anti-fouling ability was experimentally demonstrated for the first time.